L’« État-actionnaire » et le plasma - Fabrice Colomb (Revue de la Régulation)
Commodification of the human body does not make for a pretty picture if we read through the sequence of France’s bioethical laws. But this work goes beyond appearances and focuses on the case of plasma. Government as a shareholder in the national plasma industry has contributed to turning plasma into a commodity. This paper traces the origins of the state’s shareholding in the sector through the transformation of the national corporation into a public limited company. The “shareholder state” takes on two faces as the “entrepreneurial state” and the “competitive state” thereby shaping up a sector for international competition in the bioeconomy. A qualitative survey reveals how the “shareholder state” has gone about making plasma commensurable with inert substances by providing it with an exchange value. To this end, the “shareholder state” produces a euphemistic discourse to legitimize the process.